BALF cytokines in different phenotypes of chronic lung allograft dysfunction in lung transplant patients. Issue 3 (27th January 2017) - Berastegui, Cristina; Gómez‐Ollés, Susana; Sánchez‐Vidaurre, Sara; Culebras, Mario; Monforte, Victor; López‐Meseguer, Manuel; Bravo, Carlos; Ramon, Maria‐Antonia; Romero, Laura; Sole, Joan; Cruz, Maria‐Jesus; Román, Antonio
Abstract: The long‐term success of lung transplantation (LT) is limited by chronic lung allograft dysfunction (CLAD). Different phenotypes of CLAD have been described, such as bronchiolitis obliterans syndrome (BOS) and restrictive allograft syndrome (RAS). The purpose of this study was to investigate the levels of cytokines and chemokines in bronchoalveolar lavage fluid (BALF) as markers of these CLAD phenotypes. BALF was collected from 51 recipients who underwent (bilateral and unilateral) LT. The study population was divided into three groups: stable (ST), BOS, and RAS. Levels of interleukin (IL)‐4, IL‐5, IL‐6, IL‐10, IL‐13, tumor necrosis factor alpha (TNF‐α), interferon‐gamma (IFN‐γ), and granulocyte‐macrophage colony‐stimulating factor (GM‐CSF) were measured using the multiplex technology. BALF neutrophilia medians were higher in BOS (38%) and RAS (30%) than in ST (8%) ( P =.008; P =.012). Regarding BALF cytokines, BOS and RAS patients showed higher levels of INF‐ γ than ST ( P =.02; P =.008). Only IL‐5 presented significant differences between BOS and RAS ( P =.001). BALF neutrophilia is as a marker for both CLAD phenotypes, BOS and RAS, and IL‐5 seems to be a potential biomarker for the RAS phenotype.